Sistem Informasi Penjadwalan Mata Pelajaran Pada SMPIT Darul Qur’an - Alfiansyah; Yudi Kurniawan (CV. Multi Kreasi Media, 2023)
SMPIT Darul Qur'an is an institution engaged in education at the level of Islamic Boarding Schoolbased Junior High School with IT (Integrated Islam) level in Pabuaran, Kec. Mount Sindur, Kab. Bogor, West Java. In carrying out its activities, SMPIT Darul Qur'an is under the auspices of the Ministry of Education and Culture. Currently, SMPIT Darul Qur'an does not yet have an information system in the form of a website, because it still uses a conventional system. This conventional system is considered inappropriate because it still uses a lot of paper and is impractical. The current system is running, the Deputy Head of Curriculum makes a schedule of subjects using Microsoft Excel, then when the schedule for the subject has been made then the Deputy Head of Curriculum saves the schedule of these subjects in pdf form. The next process is that the deputy head of the curriculum prints the subject schedule and distributes it to teachers who teach in class. Therefore, the purpose of this research is to create a subject scheduling information system, which can help teachers find out the schedule of subjects according to class hours and guardians of students (parents) to monitor the class schedule.